Development of Cooperative Integrated Reading and Composition Learning Model with Mind Mapping Method to Improve Students' Understanding of Mathematical Concepts - Nurul Fauziah; Nurma Izzati; Hendri Handoko (Journal of General Education and Humanities, 2022)
The development of the CIRC learning model with the mind mapping method was based on the needs analysis results. The findings include that students' understanding of mathematical concepts is still not optimal, and teachers' selection of learning models is still not appropriate. The CIRC learning model applied in schools is still not optimal or has several shortcomings. The objectives of this study are: (1) to determine the development of the CIRC learning model with the mind mapping method to improve students' understanding of mathematical concepts; (2) know the improvement of students' understanding of mathematical concepts who received the application of the CIRC learning model with the mind mapping method; (3) knowing the difference in increasing students' understanding of mathematical concepts between those who received the application of the CIRC learning model with the mind mapping method and those who received the application of the CIRC learning model; (4) knowing students' responses to the application of the CIRC learning model with the mind mapping method. The results showed that: (1) the CIRC learning model with the mind mapping method was included in the valid criteria and should be tested based on the product validation results. (2) there is an increase in students' understanding of mathematical concepts in the experimental class who get the application of the CIRC learning model with the mind mapping method of 0.88 (high criteria). (3) there is a significant difference between the application of the CIRC learning model with the mind mapping method and the application of the CIRC learning model to improve students' understanding of mathematical concepts (4) The student response to the application of the CIRC learning model with the mind mapping method is 79% (very good) positive students (accept).